2000
DOI: 10.1038/sj.jhh.1001041
|View full text |Cite
|
Sign up to set email alerts
|

How well do office and exercise blood pressures predict sustained hypertension? A Dundee Step Test Study

Abstract: Exercise systolic blood pressure (BP) appears to be a better predictor of cardiac mortality than casual office BP. We tested whether this could be explained by exercise systolic BP being a better predictor of sustained hypertension than casual office BP. Exercise systolic BP was measured using the lightweight 3-min single stage, submaximal Dundee Step Test in 191 consecutive subjects (102 male, age 52 (s.d. 13) years) who were referred to a specialist hypertension clinic for assessment. Exercise systolic BP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…First, on-treatment Ex-BP may reflect a higher BP during routine daily physical activity even if the BP at rest is well controlled, thereby increasing cardiac afterload and leading to reduced regression of LVH. This explanation is supported by several previous studies which observed that Ex-BP was a marker of higher ambulatory BP 15 19. Other studies have revealed that on-treatment LVM change is more closely related to change in 24-h BP than in clinic resting BP 20 21.…”
Section: Discussionsupporting
confidence: 69%
“…First, on-treatment Ex-BP may reflect a higher BP during routine daily physical activity even if the BP at rest is well controlled, thereby increasing cardiac afterload and leading to reduced regression of LVH. This explanation is supported by several previous studies which observed that Ex-BP was a marker of higher ambulatory BP 15 19. Other studies have revealed that on-treatment LVM change is more closely related to change in 24-h BP than in clinic resting BP 20 21.…”
Section: Discussionsupporting
confidence: 69%
“…Likely contributors include intraseason weight gain, changes in dietary caloric intake and sodium consumption, intrinsic familial predisposition to hypertension, and endothelial dysfunction. Recent data indicate that impaired endothelial function correlates with exaggerated exercise BP response, 28 a marker of increased mean ambulatory BP 29 and future hypertension risk in young adults. 30 It is therefore possible that the repetitive hemodynamic stress inherent in ASF participation results in endothelial dysfunction and corollary changes in resting vascular tone.…”
Section: Discussionmentioning
confidence: 99%
“…37 Indeed, the prognostic value of the submaximal ExSBP as a better predictor of cardiac death than OBP has been confirmed in a few large retrospective studies, [38][39][40] and a prospective study is currently on-going. 41 Furthermore, the ExSBP is a better marker than OBP in defining sustained hypertension 42 and we have also recently reported that apparently healthy hypertensives with a raised ExSBP had prolonged maximum heart rate corrected QT interval independent of LV mass. 43 The implication of our findings is that more attention should perhaps be given to ExSBP to help with risk stratification and as a modifiable risk factor in hypertensive patients.…”
Section: Discussionmentioning
confidence: 85%
“…Hence it has little biological relevance in comparison to BP measured at a lighter exercise workload which could be reliably measured noninvasively 9 and provides an indication of the level of 'active' BP during the day. 42 In contrast, it is difficult to know how best to define the maximal ExSBP, whether it is the highest BP reached during exercise, BP measured as an exercise is being terminated or immediately after stopping exercise. These distinctions were rarely made clear in previous studies.…”
Section: Maximal Vs Submaximal Exercise Blood Pressurementioning
confidence: 99%